O transporte de passageiros e a configuração territorial da microrregião do planalto de Vitória da Conquista – BA - Oliveira, Uene Soares de (2006)
The present dissertation does a geographic analysis on the urban and interurban transport system in the microregion of the Plateau of Vitória da Conquista. It is the result of a research which was carried out in public organs of the sector, transport private companies, as well as of the survey of users opinions by means of a questionnaire applied on field work. The emergence and evolution of the diverse means of transportation in the studied microregion were discussed, as well as their insertion in the context of the State of Bahia, with a focus on the current role played by alternative transports. At this point, the implications due to the advent of this new modality of passengers transportation to the evolution of the system are worthy of attention. The absence of a governmental plan to promote a better integration of this microregion is evidenced, and so there is a transport system which ends up not fulfilling the needs of the population in the diverse municipalities. Therefore, we have a parallel, alternative system which simultaneously competes and complements the official one, but does not constitute an adequate alternative to render the proper service to users.